Biological Reconstruction with Liquid Nitrogen for Osteosarcoma of the Distal Tibia: A Case Report - Mujaddid Idulhaq; Fajar Baskoro Gardjito; Tanri Hadinata Wiranegara (Universitas Airlangga, 2026)
Background: Osteosarcoma, a primary malignant bone tumor, typically requires limb salvage surgery to maintain function while ensuring complete tumor resection. This case report presents a rare instance of distal tibial osteosarcoma treated through biological reconstruction utilizing liquid nitrogen.Case Report: This report describes a 17-year-old female patient who was initially diagnosed with low-grade osteosarcoma via biopsy, but was later confirmed to have high-grade osteosarcoma after undergoing wide excision and reconstruction using a liquid nitrogen-treated autograft. After the extensive removal of the tumor, the resected bone was devitalized using liquid nitrogen, followed by treatment with liquid nitrogen, reimplantation, and stabilization using double-plate fixation.Discussion: This method significantly diminished the likelihood of local recurrence while restoring both the structural integrity and biological function of the bone defect. This case highlights the benefits of biological reconstruction, specifically the use of recycled autografts with liquid nitrogen, as a cost-effective and sustainable approach for limb preservation in osteosarcoma patients. Conclusion: In this instance, biological reconstruction utilizing liquid nitrogen demonstrated efficacy as a limb salvage method. Liquid nitrogen freezing and inactivation provide a precise and effective method for devitalizing tumor bone while maintaining structural integrity and biological potential.